Toward a comprehensive theoretical framework for Shariah governance in Islamic financial institutions - Sheikh Obid, Siti Normala; Naysary, Babak (Palgrave Macmillan Ltd., 2014)
The purpose of this research is to develop a comprehensive theoretical framework for interpreting Shariah governance mechanism in Islamic financial institutions (IFIs). After reviewing existing theories that were used to explain the phenomenon of corporate governance, three most commonly used theories in the corporate governance and Shariah governance area namely agency theory, stewardship theory and stakeholder theory were used and integrated based on their interrelated concepts and their relationship with Shariah governance. The constructed theoretical framework includes five concepts, namely accountability, disclosure and transparency, competency, confidentiality and independency among the key functionaries in Shariah governance, which are perceived to be the principles of Shariah governance. This research is among the first attempts to build an integrated theoretical foundation for Shariah governance in IFIs and the developed theoretical framework can be used as the basis for interpretations and comparisons on the ideal versus practical situation of Shariah governance in IFIs.